2022
DOI: 10.2486/indhealth.2021-0276
|View full text |Cite
|
Sign up to set email alerts
|

Walking the tightrope between work and home: the role of job/home resources in the relation between job/home demands and employee health and well-being

Abstract: The present study investigated the role of job/home resources in the relation between job/home demands and exhaustion, job satisfaction, work-home interference, and home-work interference during the COVID-19 pandemic. We explored the prevalence of job/home demands and resources during the COVID-19 pandemic, and examined whether working at different locations (i.e., working from home or at the office) affects how both job/home demands and resources are associated with employees' health and well-being. An online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Hence, our study alleviates this shortage. Second, our results showed that perceived organizational support positively predicts occupational well-being and occupational commitment, thus supporting the motivational process of job resources in the JD-R model, that is, job resources contribute to positive job outcomes [ 22 ].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Hence, our study alleviates this shortage. Second, our results showed that perceived organizational support positively predicts occupational well-being and occupational commitment, thus supporting the motivational process of job resources in the JD-R model, that is, job resources contribute to positive job outcomes [ 22 ].…”
Section: Discussionmentioning
confidence: 54%
“…The first is the energy-driven process (demand-loss for work), and the second is the motivation-driven process (resource-gain for work) [ 21 ]. Job demands refer to job-related tasks that require immediate or long-term efforts, whereas job resources can be defined as job-related means that can be utilized by employees when they must deal with job demands [ 22 ]. Work resources have motivation characteristics that can stimulate individual motivation and improve work engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Job demands and Job resources were assessed using the Demand-Induced Strain Questionnaire (DISQ) 4,5 , which has been well-validated in different languages and various occupational sectors. The Chinese version was applied in the present study 20 Psychosocial Safety Climate (PSC) was assessed with the Chinese version 1 of the PSC-12 scale 21 . An example item is "Senior management acts decisively when a concern over an employee's psychological status is raised".…”
Section: Methodsmentioning
confidence: 99%
“…This idea corresponds to the matching hypothesis (de Jonge and Dormann, 2003), according to which the effectiveness of resources in improving employee wellbeing or protecting employees from experiencing strain is contingent upon their alignment with the specific demands or stressors employees face. For example, a crosssectional study by Ji et al (2023) indicated that resources from the work and home domains were associated with employee health and wellbeing during COVID-19 when they matched with work and home demands, respectively. In our study, we understood personal COVID-19's impact as a demand comprising health concerns, financial threats, social isolation, and difficulties with relationships at home.…”
Section: Theoretical Implicationsmentioning
confidence: 99%